Strengthening of Brick Masonry with Welded Wire Mesh - Umamaheswari, V; Kanchidurai, S; A. Krishnan, P; Baskar, K (International Journal of Engineering and Technology, 2018)
Unreinforced brickwork (URM) is the most established development method. URM being weak can't withstand the parallel burdens amid a seismic region. Consequently, it is important to locate an appropriate low-cost technique to fortify existing brickwork structures. In this paper flexural bond strength test was conducted on the rectangular brick masonry prisms with two types of welded wire meshes (epoxy coated mesh with the spacing of 12mm and galvanized iron wire mesh with the spacing of 15mm). Masonry prisms were cast and tested as per the guidelines are given in ASTM E518 /E518-15 standards. The results of the flexural bond strength embedded masonry prism show greater when comparing the prisms with no mesh embedment.